The Effect of Using Mobile Applications in Treating Learning Difficulties Among Students in Jordan - Alzubi, Khaled Ahmed Aqeel (International Journal of Interactive Mobile Technologies (iJIM), 2023)
In today’s digital era, interactive learning media is the right solution to improve the quality of effective and efficient learning. An active engagement between students and learning media using iSpring Suite can enhance student understanding and enthusiasm and motivate students in teaching and learning. This research aims to create Android-based interactive media using iSpring Suite for electric lighting installation learning materials. This research uses the Research and Development (R&D) method with a 4-D development model. This research consists of several stages: defining, designing, developing, and disseminating, and was conducted using validation sheet instruments. The results of this study indicated that the learning media experts confirmed that it was 93.8% valid. At the same time, the materials experts confirmed that it was 90.8% valid. Based on the validity percentage, Android-based interactive learning media using iSpring Suite is highly recommended for electric lighting installations subject. It has been well-tested and effectively applied as an Android-based interactive learning medium.